Efek Penambahan Mineral Zn Terhadap Gambaran Hematologi pada Anak Sapi Frisian Holstein - Sus Derthi Widhyari; Anita Esfandiari; Agus Wijaya; Retno Wulansari; Setyo Widodo; Leni Maylina (Institut Pertanian Bogor, 2014)
The objective of this experiment was to determine the effects of zinc supplementation on health status in dairy calves. Nine Frisian Holstein (FH) at 6-10 months of age were used in this experiment and divided into three groups. First group (no added Zn) for control, the second group was added 60 ppm Zn, and the third group was added 120 ppm Zn. Zn was administered daily for three months. Blood samples were collected from the jugular vein and anticoagulated with EDTA. Whole blood were used for measuring erythrocytes, hemoglobin concentration, hematocrit value, total leukocyte count, and leukocyte cell types. The results showed that no difference among groups for hematological parameters and the value of hematology were in the range values references. In conclusion, 60 and 120 ppm Zn supplementation in the feed is relatively safe for health.